Linear differential-functional equations with absolutely unstable solutions - Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.929For linear differential-functional equations of retarded and neutral types with infinitely many deviations and self-adjoint operator coefficients, we present necessary and sufficient conditions for the absolute instability of the zero solutions.